2016
DOI: 10.1007/978-3-319-17413-6_2
|View full text |Cite
|
Sign up to set email alerts
|

The European Twin Sovereign Debt and Banking Crises

Abstract: Europe currently faces a severe economic and financial Great Crisis. It is often described as a sovereign debt crisis, but in fact it is really a sequence of interactions between sovereign problems and banking problems that caused a severe economic slowdown. It also caused a fragmentation of euro area financial markets. The explanation of the crisis focuses on the imbalances of European Monetary Union (EMU) countries balance-of-payments, where TARGET2 payment system became crucial, reflecting funding stress in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The sovereign debt crisis of 2008 has contributed to the instability of the sector [9]. [10] argues that there is a strong interdependence between sovereign credit and banking systems. [11] found in their empirical study that the crisis had a significant impact on worldwide mergers and acquisitions, and more significantly they found that the emerging market banks acquired banks targeting neighboring countries and European countries.…”
Section: The Banking Sector In Europementioning
confidence: 99%
“…The sovereign debt crisis of 2008 has contributed to the instability of the sector [9]. [10] argues that there is a strong interdependence between sovereign credit and banking systems. [11] found in their empirical study that the crisis had a significant impact on worldwide mergers and acquisitions, and more significantly they found that the emerging market banks acquired banks targeting neighboring countries and European countries.…”
Section: The Banking Sector In Europementioning
confidence: 99%
“…As some European countries were experiencing macroeconomic imbalances, the US Subprime crisis created the conditions for the emergence of the EA sovereign debt crisis (Moro, 2016). Trade links between both Europe and the USA and within Europe facilitated the propagation of the Subprime crisis to Europe (European Commission, 2009).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%